Citizen participation in the management plan of the Misahuallí monkeys: an applicable example as a strategy for the conservation of urban primates in Ecuador - Álvarez-Solas, Sara; Rodríguez, Renata; Narváez-Arguello, Sofia; Valladares-Suntasig, Francisco; Viteri-Cuenca, Victoria; Vera-Guerrero, Karla; Torres-Capelo, Tamia Camila (Folia Primatologica, 2025)
Uncontrolled urban sprawl is leading to loss of ecosystems and the degradation of habitats for many species. This, along with wildlife trafficking is pushing primates to live closer to urban areas, resulting in conflicts between humans and animals. To promote peaceful coexistence, environmental education is crucial. In 2018, we launched an educational initiative aligned with Jane Goodall’s Roots and Shoots Educational Program, founded by Jane Goodall and developed by Jane Goodall Institute worldwide. Nowadays, our environmental educational group’s efforts aim to cover the ecological education aspect of the Ecuadorian Primate Conservation Action Plan. One of our key campaigns is the Misahuallí Capuchin Monkey Management Plan. Misahuallí is surrounded by Kichwa communities and is a hub for illegal trafficking. The city has been home to a group of capuchin monkeys since the late 1970s, becoming a town symbol and an important tourist attraction. However, the population has dwindled in recent years due to different pressures related to the urban environment, such as electric cables, road kills, conflicts with domestic animals, bad food provided, and sickness transmitted through direct interaction with humans. This context presents a unique opportunity to improve animal welfare, respect, illegal trafficking, and the correct human treatment of wildlife, specifically towards the capuchin monkeys’ group. Our results show increased local awareness of these issues following the project. These findings highlight the importance of engaging a committed local team, establishing long-term educational programs to ensure conservation actions’ sustainability, and local authorities’ crucial role in allocating budgets to strengthen public policy frameworks.
Keywords: capuchin monkeys; coexistence; action plan; workshops; local empowerment